Expectations of the user of mototaxi services for the promotion of receptive tourism in the city of Tarapoto - Cruz Tarrillo, Jose Joel (2020)
Objective: To know the expectations of the tourist as a user of the motorcycle taxi service in thecity of Tarapoto, using the principal component analysis technique. Method: A descriptive levelresearch was analyzed, with a non-experimental cross-sectional research design. The sample wasmade up of 150 tourists using the motorcycle taxi service. The variable “motorcycle taxi serviceexpectations” was grouped into four main components that include 59.03% of the total varianceexplained. Results: The main components found for the model are called: component 1, drivercompliance; component 2, passenger comfort; component 3, personal image of the driver andcomponent 4, respect for the environment. Conclusions: The tourist user of the motorcycle taxiservice expects priority compliance with the rules of the driver and the comfort of the trip, since thesetwo components explain 39% of the variable.